Pemberian Edukasi dengan Media Permainan Teka-Teki Silang dan Pengetahuan Kesiapsiagaan Siswa Menghadapi Bencana Gempa Bumi dan Tsunami - Ni Wayan Ari Rahayuni; I Made Mertha; I Gusti Ayu Ari Rasdini (Jurnal Gema Keperawatan, 2022)
Indonesia is a country prone to earthquakes and tsunamis. Children are a vulnerable group affected by disasters, so the importance of disaster education for children. This study aims to determine the effect of providing education using crossword puzzle games on students' knowledge of preparedness for the earthquake and tsunami disaster at SDN 1 Subagan Karangasem in 2021. This study was a pre-experimental design with a pre post test one group. Data analysis with willcoxon test. The study was conducted from March 28, 2021 to April 26, 2021. Using a total sampling technique, the number of samples was 52 people. The inclusion criteria for the sample were fourth and fifth grade students at SDN 1 Subagan. Data was collected using a disaster preparedness questionnaire. The results showed that the knowledge of preparedness before treatment was 29 people (55.8%) in the poor category and after treatment as many as 50 people (96.2%) in the good category. disaster (sig=0,000 ; p value=0,05). Based on the results of the study, it is suggested that teachers can continue to provide disaster education on a regular basis to school students with media providing materials that are more interesting, effective, and efficient.